2012
DOI: 10.1016/j.chom.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

An Atlas of the Epstein-Barr Virus Transcriptome and Epigenome Reveals Host-Virus Regulatory Interactions

Abstract: Epstein-Barr Virus (EBV), which is associated with multiple human tumors, persists as a minichromosome in the nucleus of B-lymphocytes and induces malignancies through incompletely understood mechanisms. Here, we present a large-scale functional genomic analysis of EBV. Our experimentally generated nucleosome positioning maps and viral protein binding data were integrated with over 700 publicly available high-throughput sequencing data sets for human lymphoblastoid cell lines mapped to the EBV genome. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
263
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(280 citation statements)
references
References 68 publications
15
263
2
Order By: Relevance
“…), or cells being in a particular phase of the cell cycle [42] , which could be a frequent event for rapidly replicating cells or a very infrequent event for slowly replicating cells, as for liver cells. Recent evidence reveals that in an EBV latency model lytic genes can be transcribed to considerable levels [43] , contrary to what had been thought previously. Similarly in Kaposi sarcoma virus associated tumors, subpopulations of cells express lytic gene products within a general latency setting [44] , suggesting the distinction between latency and lytic transcription is less clear cut than expected.…”
Section: A Mechanism For Tumor Initiation In Viral Persistencecontrasting
confidence: 40%
“…), or cells being in a particular phase of the cell cycle [42] , which could be a frequent event for rapidly replicating cells or a very infrequent event for slowly replicating cells, as for liver cells. Recent evidence reveals that in an EBV latency model lytic genes can be transcribed to considerable levels [43] , contrary to what had been thought previously. Similarly in Kaposi sarcoma virus associated tumors, subpopulations of cells express lytic gene products within a general latency setting [44] , suggesting the distinction between latency and lytic transcription is less clear cut than expected.…”
Section: A Mechanism For Tumor Initiation In Viral Persistencecontrasting
confidence: 40%
“…We have previously found that this CTCF-cohesin site formed a DNA-loop interaction with OriP (38). We used chromosome conformation capture (3C) and shRNA depletion studies to show that cohesin is important for DNA long-range interactions and that this protein complex also contributes to LMP1 and LMP2A transcription efficiency.…”
mentioning
confidence: 99%
“…In EBV, CTCF binds at several key regulatory regions, many of which are cooccupied by cohesin (38)(39)(40). In particular, CTCF and cohesin can bind to the LMP1 and LMP2A control region at a position within the first intron of LMP2A and the 3= untranslated region (3=UTR) of LMP1 (38) (Fig. 1A to C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given its nuclear location, we recently probed EBER2's association with chromatin (Lee et al 2015) using capture hybridization analysis of RNA targets (CHART), a technique similar to chromatin immunoprecipitation that allows RNA localization to specific sites on DNA (Simon et al 2011). EBER2 was found to bind to the so-called terminal repeats (TRs) of the EBV genome, overlapping previously identified binding sites for the cellular transcription factor paired box protein 5 (PAX5) (Arvey et al 2012). PAX5 is a well-characterized master regulator of B-lymphocyte development and function (Medvedovic et al 2011).…”
mentioning
confidence: 99%